2011
DOI: 10.1136/bmj.d1580
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reduction in working hours for doctors in training on postgraduate medical education and patients' outcomes: systematic review

Abstract: Objectives To determine whether a reduction in working hours of doctors in postgraduate medical training has had an effect on objective measures of medical education and clinical outcome. Design Systematic review. Data sources Medline, Embase, ISI Web of Science, Google Scholar, ERIC, and SIGLE were searched without language restriction for articles published between 1990 and December 2010. Reference lists and citations of selected articles. Study selection Studies that assessed the impact of a change in duty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
165
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(172 citation statements)
references
References 89 publications
4
165
1
1
Order By: Relevance
“…2 Several studies of resident education reported decreased operative experience among surgical residents after 2003, but resident burnout appears to have improved. In summary, these findings and those of another systematic review 6 suggest that the 2003 rules did not have a meaningful effect, either favorable or unfavorable, on patient safety and quality-related outcomes. Of course, this conclusion begs many questions, including whether the 2003 rules showed little impact on patient outcomes because they were too strict (causing handoff-related harms that canceled out any benefit), because they were too lax (allowing fatigued residents to continue harming patients), or because patient outcomes are inherently insensitive to duty-hour regulation (given reasonable safeguards and redundancies provided by nurses, other trainees, and faculty).…”
mentioning
confidence: 63%
“…2 Several studies of resident education reported decreased operative experience among surgical residents after 2003, but resident burnout appears to have improved. In summary, these findings and those of another systematic review 6 suggest that the 2003 rules did not have a meaningful effect, either favorable or unfavorable, on patient safety and quality-related outcomes. Of course, this conclusion begs many questions, including whether the 2003 rules showed little impact on patient outcomes because they were too strict (causing handoff-related harms that canceled out any benefit), because they were too lax (allowing fatigued residents to continue harming patients), or because patient outcomes are inherently insensitive to duty-hour regulation (given reasonable safeguards and redundancies provided by nurses, other trainees, and faculty).…”
mentioning
confidence: 63%
“…Further search using search terms and Boolean searches to identify research articles relevant to one or more of the themes produced 342 citations and one narrative review. 11 Search of the references of these studies identified another 14 citations. With further analysis, articles were selected wherein interventions relevant to one or more of the three themes were studied, resulting in a final selection of 56 citations Twenty-one studies analyzed transitions in, during, and after residency education; 19 studies addressed the educational effects of duty hour limits, [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] and 16 articles presented research on use of the competencies in teaching and assessing anesthesiology residents.…”
Section: Methodsmentioning
confidence: 99%
“…66 This has demonstrated some benefit, though studies have not shown that duty hour limits have resulted in safer care in teaching hospitals, 67,68 and in a recent review, studies were found with improved patient care outcomes, with worsening outcomes after duty hour limits, and with a number showing no change. 11 In the same review, the educational outcomes of duty hour limits were also analyzed and significant problems were found with study quality. Aside from a small number of studies that assessed performance on standardized tests, there were no data on the impact that the reduction in residents' hours would have on the acquisition of competence for independent practice, 11 potentially because true educational outcomes can be studied only years after the standards have been implemented.…”
Section: Duty Hour Limits and The Acquisition Of Competencementioning
confidence: 99%
See 1 more Smart Citation
“…Going forward, I think the question of what drives the choices of medical students is going to be less critical than the issue of what effect the 80-hour workweek has on the training, and ultimately the competence, of residents. Two large meta-analyses of the current literature have been somewhat contradictory and inconclusive [7,8]. In Britain, a competency-based, rather than time-limited, orthopaedic residency has been introduced [9].…”
Section: How Do We Get There?mentioning
confidence: 99%